(untitled) (Altre Modernità, 2022)
The issue of perpetrators has received little attention from researchers. In recent years, however, it has gained relevance both internationally and regionally. Chile is an exception in this new context, as few works have been devoted to the subject. The case of torturers has been almost absent in studies on the dictatorship. The present text seeks to enter this unexplored terrain with the intention of drawing up an initial proposal of profiles of torturers. Five main groups of torturers are proposed: the believers, the mercenaries, the bureaucrats, the sufferers and the indifferent. In the context of the description of each of them, eleven other specific profiles are also recognized: fanatics, converts, profiteers, opportunists, obedient, routine, professionals, conformists, collaborators, cynics and reckless.